An overview of the role of selpercatinib and pralsetinib in RET-fusion-positive non-small cell lung cancer (NSCLC). (March 2023) - Nguyen, Vanessa Quang; Geirnaert, Marc
Objective: Selpercatinib and pralsetinib are new targeted therapies used to treat patients with non-small cell lung cancer (NSCLC) due to RET gene rearrangements. The objective of this article is to review selpercatinib and pralsetinib in the context of RET-fusion-positive NSCLC. Data sources: The pivotal LIBRETTO-001 and ARROW trials were evaluated regarding the use of selpercatinib and pralsetinib as treatment for RET-fusion-positive NSCLC. Comparative studies, review articles and current studies on selpercatinib and pralsetinib in RET-fusion-positive NSCLC were searched on pubmed.org and scholar.google.com using "selpercatinib, " "pralsetinib, " and "NSCLC" as keywords. Product monographs were searched on google.ca and uptodate.com using the keywords "selpercatinib, " "pralsetinib, " and/or "monograph." Data summary: Selpercatinib and pralsetinib are orally administered highly selective RET inhibitors approved by the FDA following the accelerated approvals granted due to the pivotal LIBRETTO-001 and ARROW trials which evaluated selpercatinib and pralsetinib, respectively. Both drugs have shown efficacy for brain metastases and are primarily metabolized by CYP3A4 through hepatic metabolism. The most common grade 3 or 4 adverse effects of selpercatinib were hypertension, increased ALT level, and increased AST level while for pralsetinib, it was neutropenia, hypertension, and anemia. The safety profile shows similarities in severity and tolerability but additional monitoring for QT prolongation in patients on selpercatinib is recommended, compared to the risks of interstitial lung disease or pneumonitis for patients on pralsetinib. Conclusions: Overall, the increased use of selpercatinib and pralsetinib has led to the implementation of these drugs in the clinical practice of healthcare professionals such as pharmacists.